Interactions of the OX-2 lymphoid/neuronal glycoprotein - Wright, G; Wright, Gavin James (1999)
﻿ Lymphocytes play a key role in the mammalian immune system and migrate around the body interacting with both soluble factors and tissues in their role of detecting and eliminating disease causing pathogens. These interactions are mediated by the molecules expressed at the cell surface of the leukocyte which have become a popular paradigm for the study of intercellular communication. Proteins which belong to the immunoglobulin superfamily (IgSF) are the most abundant of these cell surface molecules and one of these (OX-2) is the major focus of this thesis. The OX-2 glycoprotein is expressed in both the neuronal and lymphoid compartments of rats and has no known function. However, a highly avid OX-2 binding reagent was previously shown to specifically interact with a cell surface receptor expressed by macrophages. A monoclonal antibody, MRC OX-102, which bound rat macrophages and blocked the binding of OX-2 was raised and used to molecularly identify the receptor on the macrophage by a combination of protein purification and PCR-based strategies. The rat OX-2 receptor (OX-2R) was identified as a novel member of the IgSF and had a close evolutionary relationship to the OX-2 protein itself. The two glycoproteins interacted with an affinity of 2.5μM and Koff 0.8 sec-1, values typical of interactions between cell surface proteins. A mouse form of the OX-2 receptor was also cloned. The cytoplasmic region of the OX-2R contained conserved tyrosine residues which were shown to be phosphorylated upon pervanadate treatment of macrophages. Preliminary distribution data suggest that the receptor is restricted to cells of myeloid origin and the functional consequences of the interaction are discussed. A monoclonal antibody, MRC OX-104, was raised to the human OX-2 protein to initiate the translation of this work from rodent models to humans. OX-2 showed highly conserved patterns of expression between the two species.